CONSUMER PRICE INDEX ANALYSIS IN INDONESIA - Zubaidah Nasution (PT. Arsil Reka Engineering, 2023)
The purpose of this study is to analyze the consumer price index in Indonesia and identify the factors that contribute to changes in consumer prices. This research will involve statistical and econometric analysis to identify the relationship between the CPI and important variables such as money supply, interest rates, GDP, exchange rates, and other relevant factors. This research is a qualitative descriptive study with a literature study method through literature studies sourced from journals of previous research results, using time series data from 2003 to 2022 obtained from the Central Statistics Agency (BPS) and Bank Indonesia. The results of this study explained that the money supply, interest rates, gross domestic product and exchange rates have a close relationship with the consumer price index variable in Indonesia